2019
DOI: 10.1016/j.tem.2019.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Are Lifestyle Therapies Effective for NAFLD Treatment?

Abstract: Nonalcoholic fatty liver disease (NAFLD) is becoming the most common liver disorder worldwide. Specifically, nonalcoholic steatohepatitis (NASH) and fibrosis pose an enormous burden for patients and health-care systems. In the absence of approved pharmacological therapies, effective lifestyle interventions for NAFLD, such as dietary strategies and exercise training, are currently the therapeutic strategies of choice. This review covers the influence of macronutrient quality and quantity (i.e., low-carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 63 publications
(71 reference statements)
0
75
0
4
Order By: Relevance
“…Resistance exercise for 8 weeks reduces hepatic lipids in NAFLD patients [141], and 3 months of resistance training reduces liver fat content in NAFLD patients, but without a significant change in weight [142]. Interestingly, combined aerobic and resistance training improves aerobic capacity and skeletal muscle strength, and may be the most effective exercise program for improving NAFLD [143].…”
Section: Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Resistance exercise for 8 weeks reduces hepatic lipids in NAFLD patients [141], and 3 months of resistance training reduces liver fat content in NAFLD patients, but without a significant change in weight [142]. Interestingly, combined aerobic and resistance training improves aerobic capacity and skeletal muscle strength, and may be the most effective exercise program for improving NAFLD [143].…”
Section: Exercisementioning
confidence: 99%
“…As mentioned above, the macronutrient composition of the diet also appears to be important; saturated fatty acids and simple sugars damage the liver, whereas MUFAs, PUFAs, and dietary fiber induce beneficial hepatic effects [167]. More recently, studies have underscored that meal timing and frequency may also be important [143]. Studies in rodents have suggested that intermittent fasting and restricted feeding can have beneficial effects on NAFLD, and the few human studies agree that regular meals combined with regular fasting periods may provide physiological benefits (inflammation, circadian rhythm, autophagy, stress resistance, and gut microbiota) [168].…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…A better understanding and appreciation of the diverse role of lipid metabolism in the many liver cell types will be key to prevent, halt, or cure liver fibrosis in the future. Lifestyle interventions such as lowering the caloric uptake and improving exercise are useful strategies to prevent or limit the risk for NAFLD [ 172 ]. However, pharmacological strategies to target NAFLD represent an attractive alternative in view of the increasingly large number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematically speaking, the most cost-effective means to overcome organ shortage is related to lifestyle changes (prevention of liver diseases) and the stimulation to acquire more donor organs [39]. Although cost-effective in theory and in view of the highly effective current HCV-treatment regimens improvements are expected, donor shortage will remain an obstacle in the years to come.…”
Section: The Next Hurdle Toward the Finishmentioning
confidence: 99%